Sorption isotherms of pears using different models. - Guiné, Raquel (2013)
In the present work the desorption isotherms of two varieties of pears produced in Portugal were determined for the temperatures of 20, 30 and 40 ºC. This range of temperatures was selected because it covers the range of average daily temperatures in Portugal in the summer, when the solar drying of pears takes place. The data obtained was fit using an orthogonal distance regression algorithm (ODR) to five different models found in literature, namely Chen, Guggenheim-Anderson-deBoer (GAB), Halsey, Henderson and Oswin. From the present work was possible to conclude that the two varieties of pears studied show a similar behaviour, and that at constant moisture content an increase in temperature enhances water activity. From comparing the different models was possible to conclude that the Oswin model is less appropriate for describing the processes at study, and that the Chen and Halsey models are also not very adequate. The Henderson and the GAB models, and this last in particular, revealed to be very good at describing the different situations at study.